Common Marmosets: A Potential Translational Animal Model of Juvenile Depression - Galvão-Coelho, Nicole Leite; Galvão, Ana Cecília de Menezes; Silva, Flávia Santos da; Sousa, Maria Bernardete Cordeiro de (Frontiers in Psychiatry, 2017)
Major depression is a psychiatric disorder with high prevalence in the general population, with increasing expression in adolescence, about 14% in young people. Frequently, it presents as a chronic condition, showing no remission even after several pharmacological treatments and persisting in adult life. Therefore, distinct protocols and animal models have been developed to increase the understanding of this disease or search for new therapies. To this end, this study investigated the effects of chronic social isolation and the potential antidepressant action of nortriptyline in juvenile Callithrix jacchus males and females by monitoring fecal cortisol, body weight, and behavioral parameters and searching for biomarkers and a protocol for inducing depression. The purpose was to validate this species and protocol as a translational model of juvenile depression, addressing all domain criteria of validation: etiologic, face, functional, predictive, inter-relational, evolutionary, and population. In both sexes and both protocols (IDS and DPT), we observed a significant reduction in cortisol levels in the last phase of social isolation, concomitant with increases in autogrooming, stereotyped and anxiety behaviors, and the presence of anhedonia. The alterations induced by chronic social isolation are characteristic of the depressive state in non-human primates and/or in humans, and were reversed in large part by treatment (DPT phase) with an antidepressant drug (nortriptyline). Therefore, these results indicate the C. jacchus as a potential translational model of juvenile depression by addressing all criteria of validation.